Ablation of mixed lineage kinase 3 (Mlk3) does not inhibit ototoxicity induced by acoustic trauma or aminoglycoside exposure - Polesskaya, Oksana (2010)
Jun N-terminal kinase (JNK) is activated in cochlear hair cells following acoustic trauma or exposure to aminoglycoside antibiotics. Blockade of JNK activation using mixed lineage kinase (MLK) inhibitors prevents hearing loss and hair cell death following these stresses. Since current pharmacologic inhibitors of MLKs block multiple members of this kinase family, we examined the contribution of the major neuronal family member (MLK3) to stress-induced ototoxicity, using Mlk3(−/−) mice. Immunohistochemical staining revealed that MLK3 is expressed in cochlear hair cells of C57/BL6 mice (but not in Mlk3(−/−) animals). After exposure to acoustic trauma there was no significant difference in DPOAE and ABR values between Mlk3(−/−) and wild-type mice at 48 hours following exposure or 2 weeks later. Susceptibility of hair cells to aminoglycoside toxicity was tested by exposing explanted utricles to gentamicin. Gentamicin-induced hair cell death was equivalent in utricles from wild-type and Mlk3(−/−) mice. Blockade of JNK activation with the pharmacologic inhibitor SP600125 attenuated cell death in utricles from both wild-type and Mlk3−/− mice. These data show that MLK3 ablation does not protect against hair cell death following acoustic trauma or exposure to aminoglycoside antibiotics, suggesting that MLK3 is not the major upstream regulator of JNK-mediated hair cell death following these stresses. Rather, other MLK family members such as MLK1, which is also expressed in cochlea, may have a previously unappreciated role in noise- and aminoglycoside-induced ototoxicity.